Geoinformation as a tool in the temporal variation in oil palm farming in the northeastern region of Pará (Research, Society and Development, 2021)
Elaeis guineenses Jacq. is a monocotyledonous species, belonging to the Arecaceae family and it is in African territory and has a high commercial interest. The exploitation of oil palm in Brazil began in the state of Bahia in the 17th century and, over time, expanded to the northern Brazilian region, where it had a good adaptability due to the edaphoclimatic aspects. The supervised classification contributes to the identification for the mapping of land use and occupation through the analysis and visual interpretation of the images produced through satellites. For the execution of the work, surveys of scientific data were made, such as research and studies on the theme, for a better understanding and understanding regarding the classification of land use using responses from spectral indexes at orbital levels. The work aimed to obtain a mapping of the Agrapalma farm and to provide details on the temporal variation of changes in the distribution of land use. Images from the Google Earth Engenie platform were used and the classification was supervised using the free software Qgis. In monitoring the change in soil cover, a loss of 2.46% of vegetation was observed, an increase of 10.29% of secondary vegetation and a reduction of 8,826.09 ha of exposed soil.